2022
DOI: 10.21037/tau-22-457
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of molecular profiles of upper tract urothelial carcinoma vs. urinary bladder cancer in the era of targeted therapy: a narrative review

Abstract: Background and Objective: Although upper tract urothelial carcinoma (UTUC) shares the histological appearance of urinary bladder cancer (UBC), molecular studies suggest that UTUC and UBC represent two distinct disease entities. However, treatment approaches for UTUC are virtually extrapolated from the evidence on UBC. As targeted drugs-immune-checkpoint inhibitors, fibroblast growth factor receptor inhibitors, and antibody-drug conjugates-target specific molecules, gaining more knowledge about the target-molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
2
5
0
Order By: Relevance
“…These observations collectively imply that UTUC may exhibit a reduced response to immunotherapy when compared to bladder carcinoma. 18 The present study results showed significantly improved survival outcomes in group 2, which can now serve as an evidence of the effectiveness of ICIs in high-grade UTUC.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These observations collectively imply that UTUC may exhibit a reduced response to immunotherapy when compared to bladder carcinoma. 18 The present study results showed significantly improved survival outcomes in group 2, which can now serve as an evidence of the effectiveness of ICIs in high-grade UTUC.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, UTUC tends to exhibit the luminal papillary subtype, characterised by a relatively lower presence of immune cells, particularly T cells. These observations collectively imply that UTUC may exhibit a reduced response to immunotherapy when compared to bladder carcinoma 18 . The present study results showed significantly improved survival outcomes in group 2, which can now serve as an evidence of the effectiveness of ICIs in high‐grade UTUC.…”
Section: Discussionsupporting
confidence: 70%
“…According to the findings of Tomiyama et al, the mutation rates of TP53 and ERBB2 were positively correlated with high-grade UTUC patients [ 55 ]. Our heatmap analysis revealed a correlation between the expression of VCAN and the cell migration genes MMP9, TWIST1 and N-cadherin in UTUC patients ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several targeted therapies and antibody-drug conjugates are currently being used or developed for the treatment of BC. Nectin-4, the target of enfortumab-vedotin, is overexpressed in 83% of bladder UC [67], with lower expression correlating with lower treatment efficacy. Although nectin-4 is not specific for BC, radiolabelled enfortumab may be of interest for predicting treatment response and BC staging.…”
Section: Ici Tracers and Targeted Therapiesmentioning
confidence: 99%